Total intravenous anesthesia vs inhaled anesthetic for intraoperative visualization during endoscopic sinus surgery: a double blind randomized controlled trial. Issue 10 (10th September 2018) - Little, Michael; Tran, Victor; Chiarella, Angelo; Wright, Erin D.
Abstract : Background: Bleeding during endoscopic sinus surgery (ESS) can impair visualization and delay surgical progress. The role that anesthetic technique may have on the quality of surgical field during ESS has been previously studied. However, meta‐analyses have deemed the current literature inconclusive and lacking methodological consistency. This study was designed with these critiques in mind to assess the effect of total intravenous anesthesia (TIVA) vs inhaled anesthetic on the quality of the surgical field during ESS. Methods: This study was a double‐blind, randomized, controlled trial of 30 patients of American Society of Anesthesiologists (ASA) class 1 or 2 undergoing bilateral ESS for the primary diagnosis of chronic rhinosinusitis. In addition to standard techniques to minimize blood loss, study patients were randomized to maintenance anesthesia with intravenous propofol or inhaled desflurane. Anesthetic depth was standardized using bispectral index (BIS). The primary outcome measured was the Wormald grading scale to assess the endoscopic surgical field. Results: The use of TIVA was associated with a statistically significant reduction in mean Wormald score compared to desflurane (4.21 vs 5.53, p = 0.024). Mean Boezaart score was also lower in the TIVA arm (2.18 vs 2.76, p = 0.034). Experimental groups were homogeneous in all compared baseline characteristics. Secondary outcomes including surgical duration, time to extubation, and estimated blood loss were not found to be statistically significant between experimental groups. Conclusion: Even with all other factors implemented to optimize the surgical field, utilization of TIVA vs inhaled anesthetic still resulted in a statistically significant improvement in surgical field during ESS.